Are Related Party Transactions Red Flags? - Kohlbeck, Mark; Mayhew, Brian W. (Contemporary Accounting Research, 2017)
Abstract This study investigates whether or not related party transactions serve as “red flags” that warn of potential financial misstatement. We hand‐collect related party transactions for S&P 1500 firms in 2001, 2004, and 2007 and find a positive correlation between these transactions and future restatements, suggesting restatements are more likely when a firm engages in related party transactions. The association is concentrated among transactions that appear to reflect “tone at the top” rather than arguably more necessary business transactions. We also find RPT firms pay lower audit fees. However, “tone RPT ” firms that subsequently restate pay higher audit fees, providing evidence that auditors recognize the individual restatement risks of these firms. Our results suggest that tone‐based RPT s serve as signals of higher risk of material misstatement.